Towards the first beams from the ADIGE injector for the SPES Project. (November 2019) - Galatà, A; Roncolato, C; Bisoffi, G; Francescon, P; Bellan, L; Bermudez, J; Bortolato, D; Comunian, M; Conte, A; De Lazzari, M; Gelain, F; Marcato, D; et al.
Abstract: The ADIGE (Acceleratore Di Ioni a Grande carica Esotici) injector of the SPES (Selective Production of Exotic Species) project is now in an advanced phase of installation. Its main components have been designed following particular needs of the project: first, an Electron Cyclotron Resonance (ECR)-based Charge Breeder (SPES-CB), to boost the charge states of the radioactive ions produced at SPES and allow their post-acceleration. Then, a stable 1+ source and a complete electrostatic beam line to characterize the SPES-CB. Finally, a unique Medium Resolution Mass Spectrometer (MRMS, R=1/1000), mounted on a high voltage platform downstream the SPES-CB, to clean the radioactive beam from the contaminants induced by the breeding stage. This contribution describes the status of the injector, in particular the installation of the platform housing the MRMS, the access and safety system adopted and the first beams to be extracted from the stable 1+ source.